PENGEMBANGAN MODEL PEMBELAJARAN DISCOVERY-INQUIRY UNTUK MEREDUKSI MISKONSEPSI IPA PESERTA DIDIK SMP - Tompo, Basman; Ahmad, M Arifin; Muris, Muris (Universitas Negeri Makassar, 2016)
Misconceptions in the field of science in many areas ranging from primary level to higher education. However, the efforts made to overcome or reduce the occurrence of science misconceptions have not been successful. Therefore, the main problem of this study were (i) how the implementation of learning science at the junior high school today? (ii) how to develop the discovery inquiry learning model is valid, practical and effective way to reduce students science misconceptions at junior high school. This research is a study of R & D (research and development), which refers to the stages of development Four-D (4-D), which is the stage of define, stage of design, stage of development and the stage of dissemination. The main objective of this research is to develop a learning model discovery inquiry for reducing science misconceptions at junior high school students are valid, practical, and effective. To obtain a valid model, practical, and effective, well developed instruments and learning devices. The products resulting from this research is the model book documents and supporting learning device models. The results showed that this happens science misconception adult students in SMP Negeri 2 Maros South Sulawesi for conception of Vibration and Light. Based on trial results indicate that the discovery inquiry learning model developed have valid criteria, practical and effective. Discovery inquiry learning model is said to be valid for the assessment of all components of the learning model validator meet the elements of validity. Said to be practical for learning component discovery inquiry implemented in full, and the ability of teachers to manage learning at the high category. While discovery inquiry learning model is effective, because students experiencing science misconceptions reduction in the medium category, the activities of students in the learning achievement fulfilled the ideal time and students give positive response to the discovery inquiry learning model.Keywords : learing model, discovery inquiry, science misconception, model developmentKesalahan konsep dalam bidang IPA terjadi di banyak tempat mulai dari tingkat pendidikan dasar sampai pendidikan tinggi. Namun, upaya yang dilakukan untuk mengatasi atau mereduksi terjadinya miskonsepsi IPA belum banyak membuahkan hasil. Oleh karena itu masalah utama penelitian ini adalah (i) bagaimana pelaksanaan pembelajaran IPA pada tingkat SMP? (ii) bagaimana mengembangkan model pembelajaran discovery inquiry yang valid, praktis dan efektif untuk mereduksi miskonsepsi IPA peserta didik SMP. Jenis penelitian ini adalah penelitian R&D (research and development) yang mengacu pada tahapan pengembangan Four-D (4-D), yaitu tahap pendefinisian (define), tahap perancangan (design), tahap pengembangan (develop) dan tahap diseminasi (disseminate). Tujuan utama penelitian ini adalah mengembangkan model pembelajaran discovery inquiry untuk mereduksi miskonsepsi IPA peserta didik tingkat SMP yang valid, praktis, dan efektif. Untuk memperoleh model yang valid, praktis, dan efektif, dikembangkan pula instrumen dan perangkat pembelajaran. Produk yang dihasilkan dari penelitian ini adalah dokumen buku model dan perangkat pembelajaran pendukung model. Hasil penelitian menunjukkan bahwa terjadi miskonsepsi IPA pada peserta didik di SMP Negeri 2 Maros Sulawesi Selatan untuk materi Getaran dan Cahaya. Berdasarkan hasil uji coba menunjukkan bahwa model pembelajaran discovery inquiry yang dikembangkan telah memenuhi kriteria valid, praktis dan efektif. Model pembelajaran discovery inquiry dikatakan valid karena penilaian seluruh komponen model pembelajaran oleh validator memenuhi unsur kevalidan. Dikatakan praktis karena komponen pembelajaran discovery inquiry terlaksana seluruhnya, dan kemampuan guru mengelola pembelajaran berada pada kategori tinggi. Sedangkan model pembelajaran discovery inquiry efektif, karena peserta didik mengalami reduksi miskonsepsi IPA pada kategori sedang, aktivitas peserta didik dalam pembelajaran memenuhi unsur pencapaian waktu ideal serta peserta didik memberikan respon positif terhadap model pembelajaran discovery inquiry.Kata Kunci: model pembelajaran, discovery inquiry, miskonsepsi IPA, pengembangan model